O olhar de um designer etnógrafo aprendiz: desenvolvimento de um livro-objeto sobre o patrimônio imaterial do Cariri cearense - Santana, João Lobo Miranda Sobreira de (2023)
This work was developed with the aim of producing a book-object that communicates, promotes and values the intangible heritage of the Cariri region in the northeast of Brazil. The research was carried out using a methodology based on ethnography, applied to a design project. The combination of the two areas forms the concept of ethnographic design, which is very useful in design projects that require an insertion to understand the culture, daily life and problems of a community or region. In this way, immersive field trips and multifactorial recordings were made during visits to six cities in the Cariri region of Ceará. A spontaneous documentary photography essay was developed during the trips, as well as a field notebook used to create observation drawings, write down notes and important phrases from conversations during visits to 12 masters and artisans responsible for keeping the region's popular culture alive, in addition to participation in 5 cultural events or culturally important sites. From this, a book-object project was developed called Cariri IMERSO IMENSO, which combines graphic design, product, photography, illustration and objects collected during the visits and seeks to present this entire ethnographic experience in the region, providing interactivity and immersion for the reader with the product and the culture of the region, thus promoting the promotion and appreciation of the intangible heritage of Cariri in Ceará